Comparing environmental impacts of natural inert and recycled construction and demolition waste processing using LCA - Simion, Isabela Maria; Fortuna, Maria Emiliana; Bonoli, Alessandra; Gavrilescu, Maria (Journal of Environmental Engineering and Landscape Management, 2013)
Construction and demolition wastes (C&DW) are usually recognized as not dangerous, but their accumulation can generate serious environmental problems. In spite of C&DW high potential to be reused/recycled, the practical procedures need to be assessed in terms of environmental consequences. The objective of this study is to quantify the environmental impacts of C&DW recycling/reuse, specifically in the production of aggregate 0/30 mm, comparative to those generated during the natural inert processing, in terms of global impacts addressing the whole process and for each technological phase. The analysis was carried out using Life Cycle Assessment methodology, assisted by SimaPro software, and based on primary data collected directly from the Italian Emilia Romagna region. Three methods were used for impact quantification: Eco-Indicator 99, EDIP/UMIP and Cumulative Energy Demand. The analysis revealed that the environmental impacts generated by C&DW recycling/reuse accounting for about 40% of the impacts induced by natural inert processing.